2009
DOI: 10.1111/j.1467-7717.2009.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

The politics of protection: aid, human rights discourse, and power relations in Kyaka II settlement, Uganda

Abstract: This paper explores the conceptualisation and application of 'protection' by the United Nations High Commissioner (UNHCR), Ugandan government, and Congolese refugees in Kyaka II refugee settlement, Uganda. Analysing the origins and consequences of a demonstration against school fees, and drawing on other ethnographic data, it explores how different interpretations of this incident reflect different conceptions of, and approaches to, protection. Ugandan government officials viewed the demonstration as a securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…UNHCR (2015) makes clear its commitment to delivering protection and other forms of assistance to refugees in accordance with the legal frameworks of countries of asylum and in a fashion that supports host country governments; this suggests that at the local level, UNHCR and the government staff members involved in the practical administration of protection will (to some extent) be able to exercise agency over the interpretation and implementation of assistance. Viewing power as not just reproduced but also negotiated creates the space in which to see how it 'flows' through acts of humanitarianism, such as protection, and to explore contestations concerning protection discourse and practice (Clark-Kazak, 2010).…”
Section: Problematising Protection Discoursementioning
confidence: 99%
“…UNHCR (2015) makes clear its commitment to delivering protection and other forms of assistance to refugees in accordance with the legal frameworks of countries of asylum and in a fashion that supports host country governments; this suggests that at the local level, UNHCR and the government staff members involved in the practical administration of protection will (to some extent) be able to exercise agency over the interpretation and implementation of assistance. Viewing power as not just reproduced but also negotiated creates the space in which to see how it 'flows' through acts of humanitarianism, such as protection, and to explore contestations concerning protection discourse and practice (Clark-Kazak, 2010).…”
Section: Problematising Protection Discoursementioning
confidence: 99%
“…An example of political action by school students illustrates children's taking up of rights to which they were sensitized and their follow-through with attempts to make public claims that provoked social controversy. Clark-Kazak (2010) reported an incident that occurred in Kyaka ll Camp in Uganda. In 2004, a small group of Congolese refugee students attempted to claim free high school education.…”
Section: Claiming Of Refugee Children's Rightsmentioning
confidence: 99%
“…Some work close to the source of violence, while others intervene after people have already fled to a safer location. A study in a Ugandan refugee camp revealed, for example, that youth considers education to be a protection strategy to escape structural violence in the site (Clark-Kazak, 2010). 120-125).…”
Section: Protection Activitiesmentioning
confidence: 99%
“…That being said, protection for communities is not only limited to physical safety. A study in a Ugandan refugee camp revealed, for example, that youth considers education to be a protection strategy to escape structural violence in the site (Clark-Kazak, 2010). Regardless of the stage at which humanitarians intervene, achieving positive protection outcomes eventually depends on several factors, such as the capacity of humanitarian agencies to influence the behaviour of warring parties.…”
Section: Protection Activitiesmentioning
confidence: 99%
See 1 more Smart Citation